2020
DOI: 10.1016/j.ijdrr.2020.101843
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from the COVID-19 pandemic: Distress and resilience

Abstract: The current study analyzed repeated responses to the coronavirus. Data for the first phase was gathered during the peak of the COVID-19 pandemic crisis in Israel (T1), which included the overall lock-down of the Israeli society. The repeated measurement was conducted approximately two months later, on the initial phase of lifting the lock-down (T2). The sample size was 300 people. Results indicated four significant differences between the first and the second measurements: Sense of danger, distress symptoms, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 44 publications
9
66
0
2
Order By: Relevance
“…Recent research using Filipino samples showed stable four factors of national resilience (Callueng, Aruta, Antazo, & Diato, 2020 ). Previous studies using Israeli adults demonstrated reliability coefficients of α = .88 (Kimhi, Eshel, et al, 2020a ) and α = .91 (Kimhi, Marciano, et al, 2020b ) for national resilience during the COVID-19 pandemic. In the current study, the overall reliability of national resilience was α = .95.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…Recent research using Filipino samples showed stable four factors of national resilience (Callueng, Aruta, Antazo, & Diato, 2020 ). Previous studies using Israeli adults demonstrated reliability coefficients of α = .88 (Kimhi, Eshel, et al, 2020a ) and α = .91 (Kimhi, Marciano, et al, 2020b ) for national resilience during the COVID-19 pandemic. In the current study, the overall reliability of national resilience was α = .95.…”
Section: Methodsmentioning
confidence: 97%
“…Participants reported the extent to which they feel secured at home during the Coronavirus crisis by answering one item ( “How safe are you at your home during this period of the Coronavirus crisis?” ) using a 5-point scale (1 = Not at all to 5 = To a very great extent ). Recent studies have used this item in assessing people’s sense of safety at home in times of adversities including, during the COVID-19 crisis (Kimhi, Marciano, et al, 2020b ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The research regarding COVID-19 is the need of the hour. However, post COVID, research concentrating on community health, disaster management and pandemic prediction may increase [40,41].…”
Section: Fundingmentioning
confidence: 99%